2021
DOI: 10.1029/2020jb021262
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanocrystalline and Amorphous Materials Causes Parallel Brittle‐Viscous Flow of Crustal Rocks: Experiments on Quartz‐Feldspar Aggregates

Abstract: Relative motion of tectonic plates is accommodated along lithosphere-scale shear zones. The strength and stability of these shear zones control large-scale tectonics and the location of earthquakes (Bürgmann & Dresen, 2008;Molnar, 2020). Laboratory-derived strength profiles of the lithosphere postulate that the strength in the upper crust is controlled by frictional sliding along preexisting fractures, while the strength of the lower crust and upper mantle is controlled by viscous flow of rocks (Brace & Kohlst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 104 publications
2
10
0
Order By: Relevance
“…1a). Note that microcrystalline experiments develop patches of nanocrystalline material with increasing strain that interconnect at peak stress and allow for failure 24,30 . All experiments were conducted in a general shear geometry at temperatures, T = 200, 300 and 500 °C and confining pressures, P c = 500 MPa at a constant displacement rate of ~10 −3 mm s −1 , corresponding to a shear strain rate, _ γ; of ~10 −3 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1a). Note that microcrystalline experiments develop patches of nanocrystalline material with increasing strain that interconnect at peak stress and allow for failure 24,30 . All experiments were conducted in a general shear geometry at temperatures, T = 200, 300 and 500 °C and confining pressures, P c = 500 MPa at a constant displacement rate of ~10 −3 mm s −1 , corresponding to a shear strain rate, _ γ; of ~10 −3 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Fault weakening occurs due to the intrinsic low viscosity of the nanocrystalline fault rocks. Shearing of coarse-grained fault rocks locally leads to comminution and patchy production of nanocrystalline material 22,30 , the volume occupied by these nanocrystalline materials increases with increasing work and homologous temperature 24,45 , eventually reaching a percolation threshold. Although the extremely finegrained material is rate-strengthening, it has a much lower viscosity (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeled principal stresses, pressure, differential stress, and deformation rates also show heterogeneous patterns as observed in the experimentally produced phase and grain‐size distribution. In fact, in experimental studies, it is common to observe shear bands and zones of localized deformation not randomly distributed but rather following specific patterns (Holtzman et al., 2003; Marti et al., 2020; Pec & Al Nasser, 2021; Pec et al., 2016). In this work, we showed that the distribution of shear stress and strain is more pronounced along the short diagonal in the central part of the sample, that links the forcing‐block inner tips.…”
Section: Discussionmentioning
confidence: 99%